2018
DOI: 10.1021/acsnano.8b01086
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Profiling of Metal Oxide Nanoparticles in Liver Context Reveals Pyroptosis in Kupffer Cells and Macrophages versus Apoptosis in Hepatocytes

Abstract: The liver and the mononuclear phagocyte system are a frequent target for engineered nanomaterials, either as a result of particle uptake and spread from primary exposure sites or systemic administration of therapeutic and imaging nanoparticles. In this study, we performed a comparative analysis of the toxicological impact of 29 metal oxide nanoparticles (NPs), some commonly used in consumer products, in transformed or primary Kupffer cells (KCs) and hepatocytes. We not only observed differences between KCs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
162
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(167 citation statements)
references
References 57 publications
5
162
0
Order By: Relevance
“…As intracellular NP accumulation can result in cell death through both necrotic and pyroptotic pathways, this also allows free mtDNA and whole mitochondria to act as a danger signals when released from dying cells into the extracellular space . Should dying cells and/or their released cellular components be phagocytized, mtDNA is capable of binding to TLR9, an endosomal pattern recognition receptor (PRR) that recognizes unmethylated CpG sequences on DNA.…”
Section: Np Exposure Leads To Release Of Endogenous Danger Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…As intracellular NP accumulation can result in cell death through both necrotic and pyroptotic pathways, this also allows free mtDNA and whole mitochondria to act as a danger signals when released from dying cells into the extracellular space . Should dying cells and/or their released cellular components be phagocytized, mtDNA is capable of binding to TLR9, an endosomal pattern recognition receptor (PRR) that recognizes unmethylated CpG sequences on DNA.…”
Section: Np Exposure Leads To Release Of Endogenous Danger Signalsmentioning
confidence: 99%
“…It has been previously well described that the reactivities of different NPs are influenced by their chemical composition. This is dependent on different classes of NPs—such as transition metal oxides, soluble metal oxides, cationic/anionic liposomes, and others— as well as size, added particle coatings, and functional groups, crystalline vs. amorphous structure, and acquired biocoronas . Recent studies are shedding more light on exactly how these different chemical compositions interact with cells and subcellular components, with evidence suggesting that responses may not only be NP‐specific, but also cell‐type specific …”
Section: Introductionmentioning
confidence: 99%
“…However, their practical applications are hindered by their potential cytotoxicity, which often causes inflammation and irritation. Moreover, the antibacterial agents that are often used include traditional antibiotics and some metal nanoparticles such as silver, copper, and magnesium, which are limited by bacterial drug resistance and the potential toxic side effects of the metal ions, respectively . Therefore, biomaterials with better antibacterial properties and biocompatibility are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, in literature there are very few reports about responses of hepatic cells to sub-lethal treatment with NPs, for review see [19]. Moreover, most of the research is done utilizing only one cell line without direct comparison of the observed effects on closely related cell lines [16,19,20]. Therefore, in this study, we chose three hepatic cell lines (HepG2, Huh7, and Alexander cells).…”
Section: Effect Of Iron Oxide Nanoparticles On Cell Viability and Oximentioning
confidence: 99%